Mental Intelligence and the Complexity of Sentence Structures in the Interaction between Teachers and Children with Autism - Djatmika, Djatmika; Hikmawati, Ahfi; Sumarlam, Sumarlam (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
This article discusses the relationship between the mental intelligence of children with autism and their capability in understanding the complexity of sentence structure represented in utterances performed by their teachers. In addition, this study also explains the complexity of the sentence structure produced by the autistic children in interacting with the teachers. The data of this research are in the form of sentence structures used in the class interaction between teachers and students with autism. The collected data were then analyzed by classifying the sentences used by the teachers and the sentences produced by children with autism. The results showed that children with high mental intelligence were able to understand the complex sentence structures used by the teachers and were able to respond and speak utterances in the form of complex sentences. This shows that children with high mental intelligence understand and can produce sentences in a complex structure better than those with a low mental one.